A capabilities approach to environmental assessment: enhancing the integration of human development and well-being in participatory environmental decision making - Simpson, Nicholas Philip (Department of Environmental and Geographical Science, 2017)
Building on the work of Martha Nussbaum and Amartya Sen, this research aims to enhance integration of human development and well-being in environmental assessment through developing a capabilities approach to the practice. The research emphasises the effectiveness and equity imperatives of public participation and highlights the inclusion of appropriate social considerations in environmental decision making. The participatory focus emphasises the potential for decision shaping by stakeholders and decision support for stakeholders to participate meaningfully in environmental assessment. The research develops an evaluative framework for public participation that better considers the capabilities of stakeholders. It explores the potential consilience of the capabilities approach and that of environmental assessment, with emphasis on the principles of justice in participatory decision making. A mixed methods approach explores, tests and evaluates a selection of five South African environmental assessment case studies using an applied capabilities framework. Four main methods are employed, a discourse analysis of environmental assessment reports, a conventional Q methodology, an adapted ranking Q methodology, and a survey using Likert scales. The research findings highlight the relationship between the stakeholder's capability considerations that relate to aspects of their 'ability', 'opportunity' and 'constraints' to participation. The research ranks an array of capabilities and provides insight into the types of capabilities stakeholders value highly when reflecting on their participation experience in environmental decision making. Reflecting on the emergent findings from the cases, the research contributes to the praxis of environmental assessment through theoretical development. The theoretical framework focuses on an individual's participation capabilities as well as a broader consideration of capabilities for practice to increase the realizable opportunities, or freedoms, to choose the kinds of environmental futures that can reasonably be considered as valuable and sustainable. Capability concepts of 'ceilings', 'thresholds' and 'capability sufficiency' are commended as supplementary to existing practice specifications of 'meaningful' participation. The research commends that the capabilities approach has potential to be included as a core part of the training for assessment practitioners. It also concludes that the field of environmental assessment provides a rich empirical context for the development of a more robust sustainability-orientated capabilities approach.